Design Aesthetic in Visual Communication Effectiveness - Gina Fajri Aulia; Nanang Ganda Prawira (Edumaspul: Jurnal Pendidikan, 2024)
This research is entitled Design Aesthetics in the Effectiveness of Visual Communication (Analysis of Event Poster Finder #3 DKV UPI). It is motivated by the need for visual communication in the DKV UPI Dies Natalis event to understand the role of design elements and principles in a poster as a promotional media. Visual communication is a key element in creating effective posters and illustrations, especially when promoting events. This article analyzes the effectiveness of visual communication in the promotional poster design for the 3rd Dies Natalis event "FINDER 3" Visual Communication Design (DKV) learning program, Universitas Pendidikan Indonesia (UPI). This study examines how design elements such as typography, color, composition, and imagery are used to communicate messages effectively to target audiences. This study uses a qualitative approach with an analysis of design aesthetics in the form of design elements and design principles to understand how meaning is conveyed through visual elements. The study shows that the use of contrasting colors, typography, and balanced composition play an important role in attracting attention and making messages easier to understand. Illustrations that match the theme of the event are also important elements in adding to the appeal of posters. This article is expected to contribute to more effective and informative visual communication design practices in the future.